Determination of Forage Yield and Quality Characteristics of Annual Ryegrass Lolium multiflorum Lam. Lines - Tamer Yavuz; Mustafa Sürmen; Sebahattin Albayrak; Necda Çankaya (Journal of Agricultural Sciences)
In the present study, we examined forage yield and quality features of annual ryegrass Lolium multiflorum Lam. lines developed by using half-sib family selection breeding method. The study was conducted in a randomized complete block design with three replications between 2009 and 2011 years in Samsun, Turkey. Based on the average of the results of two years, significant differences were found for all parameters. In the studied lines and varieties, dry matter yields were found between 6.66 and 9.37 t ha-1, crude protein contents 11.46-13.81%, crude protein yields 0.80-1.18 t ha-1, acid detergent fiber 31.41-34.75%, neutral detergent fiber 48.77-52.80%, total digestible nutrient contents 56.49-60.80%, total digestible nutrient yields 376.35-556.42 t ha-1 and relative feed values 109.33-122.83. Annual ryegrass lines 4, 5, 6, 10 and 11 were selected for further regional yield assessments due to their superior yield and quality attributes